Effects of response prompts and diagram comprehension ability on text and diagram learning in a college biology course. (June 2017) - Van Meter, Peggy N.; Cameron, Chelsea; Waters, John R.
Abstract: Embedded response prompts are an effective method to support multimedia learning. Response prompts are directives situated within instructional material. Responding to these prompts affects learners' cognitive operations. Different types of prompts affect learning differently due to variations in stimulated cognitive operations. This study compared three types of experimental response prompts; prompts to self-explain the contents of a page, prompts to attend to diagrams and text-diagram relations, and prompts to self-explanation text-diagram relations; and two control conditions. Three tasks that measure verbal text knowledge, diagram knowledge, or knowledge of text-diagram relations assessed learning. The effects of diagram comprehension ability were also considered. A 5 X 3 mixed model ANCOVA revealed an interaction between prompting conditions and posttest tasks. Diagram comprehension ability was associated with task performance but did not interact with conditions. Highlights: Study tests effects of different response prompts on multimedia learning. Learners respond to the prompts that are embedded in the multimedia material. Prompts stimulating self-explanation were most effective on verbal posttest tasks. Prompts stimulating diagram awareness were most effective on diagram tasks. Combining these two types of prompts was not more effective than either alone.